Perception of Residents in Manaus on the Urban Afforestation - Yêda Maria Boaventura Corrêa Arruda; Ana Paula Rebouças de Souza; Júlia Pereira de Vasconcelos; David Lopes Neto (Centro Universitário Adventista de São Paulo, 2022)
The municipal governments, through their Environmental Secretariats, seek to invest in afforestation through public policies, educational campaigns and seedling distribution. However, the actions are inefficient, as studies on afforestation are based on inventories of species planted in public places, few studies seek to understand the population on the subject of afforestation. It is believed that the work of environmental education is of paramount importance. This study aimed to analyze the perception of afforestation of residents from different areas of Manaus, Amazonas state through an interview in the city of Manaus. Most participants were women aged 18-28 years. Most residents have completed primary education. Residents understand what urban afforestation is and the benefits of planting trees can bring, but they are not aware of the most suitable species to be buried in the city.